BACTERIAL OBSERVATION WITH GRAM STAIN ON PURE CULTURE OF BACTERIA IN URINE - Situmorang, Rahel; Syahirani, Zilan; Simanjuntak, Andreas (Universitas Negeri Medan, 2024)
Bacteria are one of the microscopic organisms contained in the urine, and the presence of bacteria in the urine we call bacteriuria. Gram painting examination of urine with a microscope is one of the good examination methods to detect the presence of bacteriuria. This study aims to identify gram-positive bacteria and gram-negative bacteria in urine using the Gram staining method. The research method used is the experimental method. This research is in the laboratory by giving treatment to the object of study. Sampling is urine, taken from the urine of one of the students of Medan State University. The results of the culture process are known that the urine sample (U4) has a coccus-shaped cell shape with a red cell color which indicates that the bacterial cells in this urine are included in the gram-negative type of bacteria. In gram-negative bacteria, the cell wall structure consists of three layers (the inner layer is peptidoglycan, one layer is murein base frame and the outer layer is lipopolysaccharide and lipoprotein), there is no teichoic acid, lysozyme softens the cell wall (detergents disorganize that wall by damaging the lipid layer), the cell wall is thin which is about 10-15 nm, less susceptible to penicillin, and not so absorbent of basic dyes but with safranin dyes (red) very absorb.